Investigating The Role Of Interprofessional Collaboration Between Physicians And Nurses In Delivering Patient -Centered Care For Individual With Chronic Illnesses (The Review of Diabetic Studies, 2024)
Chronic diseases are an important global health challenge that requires the use of patient-centered care solutions that cater to the multifaceted and dynamic needs of people with these conditions. Cooperation between nurses and physicians is increasingly recognized as the key to delivering optimal healthcare to this population. Nonetheless, the concrete processes and effects of physician-nurse teamwork on patient-centered care in the context of chronic illness management have become a significant issue, which can be defined by the absence of systematic implementation and limited evidence of interventional effectiveness at the primary care level.In this light, this study explores the concept of IPC between physicians and nurses in providing patient-centered care to individuals with chronic illnesses and how the concept impacts patient outcomes, communication, shared decision-making, and care coordination. An in-depth examination of scholarly works indicates that effective communication, mutual respect, and role definition are the main facilitators of IPC, whereas hierarchical structures, communication failure, and role ambiguity are the contributors to the barrier. It is assumed that the findings will be useful in informing practice guidelines, educational initiatives, and policies aimed at improving collaborative practices, which will eventually result in better patient experiences and health outcomes among those living with chronic conditions.